The Cult of the Dead in Chinese-Hakka Family and Society in Singkawang-West Kalimantan - M. Ikhsan Tanggok (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2004)
This paper tries to show the Chinese cultures and traditional religion in Singkawang, particularly practices connected with ancestor worship, like the burial ritual and rituals before and after burial. This paper also tries to show that life after death (unreal world) in Chinese-Hakka belief is still in connection with world life (real world or dunia nyata).